The Comparison of the Spiritual Intelligence and Self-Concept of Blinds and Sighted High School Girl Students in Tehran - Sayeh Semnanian; Anahita khodabakhshi koolaee (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objectives: Spiritual intelligence and self-concept could have a positive influence on inclusive development of high school students. The purpose of this study is to compare the spiritual intelligence and self-concept of blinds and sighted high school girls in Tehran. Materials & Methods: This research is causal-comparative study. The Statistical population of this research includes all the blind and sighted high school girl students in the Academic year of 1394-95 in Tehran. The studied sample consisted of 50 blinds and 50 sighted high school girls. The blinds were selected using the Purposive sampling and the sighted students by the available sampling. Data were collected using the spiritual intelligence questionnaire of Badiee and self-concept questionnaire of Rogers. Two main statistical methodologies were used in data analysis: descriptive statistics by using frequency distribution, percentage, mean and standard deviation, and inferential statistics using ANOVA. In this study, all relevant ethical issues were considered. Results: Results revealed that there was a significantly difference between the blinds and sighted groups in spiritual intelligence. The blinds reported significantly higher spiritual intelligence comparing to their sighted peers. However no significant difference in self-concept was observed between two groups. Conclusion:It is concluded that the perception and the attitude of blind students toward their ability are in high level and are in equal rank to their sighted counterparts. Keywords: Blinds, Self-concept, Spiritual intelligence, Students For downloading the full-text of this article please click here. Please cite this article as: Semnanian S, khodabakhshi koolaee A. The Comparison of the Spiritual Intelligence and Self-Concept of Blinds and Sighted High School Girl Students in Tehran J Res Relig Health.2017;3(1): 42- 52